I'm studying probability. This is not homework. I have been studying for a graduate master's since September 2015. The textbook is Probability : An Introduction (Grimmett & Welsh).

You are presented with two urns. Urn 1 contains 3 white and 4 black balls, and Urn 2 contains 2 white and 6 black balls. (a) You pick a ball randomly from Urn 1 and place it in Urn II. Next you pick a ball randomly from Urn 2. What is the probability that the ball is black?

I made the following reasoning.

Prob of picking black from the Urn 1 = P(B1) = 4/7
Prob of picking white from the Urn 1 = P(W1) = 3/7
Prob of picking black from the Urn 2, after placing the picked ball in it = P(B2) = ?

B1 and W1 are a partition of Omega so I can use the partition theorem:

P(B2) = P(B2|B1)*P(B1) + P(B2|W1)*P(W1)

I intuitively know that P(B2|B1) = 7/9, because, given that I picked a black ball from the Urn 1 and placed it in the Urn II, now I have 7 possibility of success and 9 possible outcomes.

I intuitively know that P(B2|W1) = 6/9 for the same reason.

Then P(B2) = 7/9*4/7+6/9*37 = 0.73

I would like to know if my reasoning is correct and what is the formal way to show that P(B2|B1) = 7/9 and P(B2|W1) = 6/9.


1 Answer 1


The formality you request uses conditional probabilities.. A probability tree is a good way to reason with them. Use it as a guide to the formal demonstration.

enter image description here

Let's begin at the end: what is the chance the ball is black? It depends on what happened before. That's the conditioning event. So:

  • Let $\mathcal B$ be the event that the first ball is black and $\mathcal B ^\prime$ be the event it is not black. Evidently $\Pr(\mathcal B) = 4/(3+4) = 4/7$ and $\Pr(\mathcal B^\prime) = 1 - 4/(3+4) = 3/7.$

  • Let $\mathcal C$ be the event that the ball selected from the second urn is black. When $\mathcal B$ occurs, the second urn has $2$ non-black and $6+1$ black balls. Otherwise, when $\mathcal B^\prime$ occurs, the second urn has $2+1$ non-black and $6$ black balls. Consequently

$$\Pr(\mathcal C\mid \mathcal B) = \frac{6+1}{2 + (6+1)} = \frac{7}{9}$$


$$\Pr(\mathcal C\mid \mathcal B^\prime) = \frac{6}{(2+1) + 6} = \frac{6}{9}.$$

Because $\mathcal B$ and $\mathcal B^\prime$ are disjoint and partition the initial outcomes, the Law of Total Probability asserts

$$\Pr(\mathcal C) = \Pr(\mathcal C\mid \mathcal B)\Pr(\mathcal B) + \Pr(\mathcal C\mid \mathcal B^\prime)\Pr(\mathcal B^\prime) = \frac{7}{9}\times \frac{4}{7} + \frac{6}{9}\times \frac{3}{7} = \frac{28 + 18}{63} = \frac{46}{63}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.